Perbedaan Pengetahuan, Sikap dan Keterampilan Sebelum dan Sesudah Pembentukan Serdadu Jentik di Sd Negeri Dalam Pencegahan Demam Berdarah Dengue - Wella Sahrei Ramadhani; Darwel Darwel; Wijayantono Wijayantono (Jurnal Sehat Mandiri, 2018)
This research is quantitative and carried out using the research design of one group Pre test posttest. The research sample was 4th grade students who became small doctors in 7 elementary schools in Surau Gadang Village. Implementation of research November - December 2018. Primary data obtained directly from filling out the research questionnaire by sample. Based on these results it can be concluded that there are differences in knowledge, attitudes and skills before and after the formation of larvae soldiers in Public Elementary Schools in the Prevention of DHF Cases in Surau Gadang Sub-District, Nanggalo District, Padang City in 2018. It is expected that the school will complete facilities such as flashlights. School Health Business Teachers supervise larva soldiers once a week. For DHF program holders the Health center can continue the DHF counseling activities to schools once a month and provide leaflets and posters about DHF